A Schistosomiasis Model with Praziquantel Resistance - Longxing Qi; Jing-an Cui (Discrete Dynamics in Nature and Society)
A compartmental model is established for schistosomiasis with praziquantel resistance. The model considers the impact of genetic resistance and drug treatment on the transmission of schistosomiasis. We calculate the basic reproductive number and discuss the existence and stability of disease-free equilibrium, boundary equilibrium, and coexistence equilibrium. Our analysis shows that regardless of whether drug treatment leads to the emergence of resistance, once the impact of genetic resistance is larger, the resistant strain will be dominant, which is detrimental to the control of schistosomiasis. In addition, once the proportion of human with drug-resistant strain produced by drug treatment is larger, the number of human and snails with resistant strain is larger. This is not a good result for drug treatment with praziquantel.